1998
DOI: 10.1046/j.1365-2648.1998.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of aftercare on chronic patients and frail elderly patients when discharged from hospital: a systematic review

Abstract: The purpose of this systematic review was an assessment of the efficacy of aftercare in chronic patients and the frail elderly when discharged from hospital, as regards quality of life, compliance, costs, medical consumption and quality of care. In pursuit of this goal, 17 publications on the effects of aftercare after discharge from hospital were examined. A systematic assessment of methodological quality by two blinded independent reviewers resulted in a consensus score (0-100 points), based on four categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
(24 reference statements)
2
13
0
Order By: Relevance
“…In reviewing the results of the study, district nurses play only a minor role in the treatment of cancer pain. These results are in agreement with a review article evaluating the beneficial effects of aftercare in chronic patients, in which it was found that a majority of the studies reported no clear beneficial effects (Bours et al. 1998).…”
Section: Resultssupporting
confidence: 91%
“…In reviewing the results of the study, district nurses play only a minor role in the treatment of cancer pain. These results are in agreement with a review article evaluating the beneficial effects of aftercare in chronic patients, in which it was found that a majority of the studies reported no clear beneficial effects (Bours et al. 1998).…”
Section: Resultssupporting
confidence: 91%
“…Almost three-quarters of the tools (73%) were 'new' (or did not state the origin of the tool) and the remainder were modifications of a single existing tool. The most commonly modified tools were Chalmers and colleagues 51 and the Maastricht Criteria list, 67 the latter having been published several times by different authors, [68][69][70][71][72][73] but originating in 1989. 74,75 Most (182) of the identified tools aimed to assess more than one study design.…”
Section: General Descriptionmentioning
confidence: 99%
“…78,79 The Jadad 46 and McMaster 80 tools did not include items in five of the six domains. In contrast, nine of the 23 tools aimed at more than one study design 73,87,[97][98][99][100][101][102][103] and with specific items according to design, plus two of the four tools designed for cohort studies, 64,66 were included in the top 60 tools. I n t e r p r e t a t i o n # 1 2 P r e s e n t a t i o n…”
Section: Figure 2 Flowchart Of Tool Selection Processmentioning
confidence: 99%
“…Prevention of disability in frail older persons is seen as a priority for research in geriatrics (Ferrucci et al 2004) and can lead to the maintenance of quality of life and reduced health care costs (Cutler 2001). Several systematic reviews are available, which focus on specific categories of interventions for frail older persons, e.g., comprehensive geriatric assessment (Wieland 2003), after-care (Bours et al 1998), or respite care (Mason et al 2007). No overview is available, however, which provides an extensive overview of the content of the full range of existing programmes for community-living frail older persons that are aimed at the prevention of disability.…”
Section: Introductionmentioning
confidence: 99%